2019
DOI: 10.4103/ajns.ajns_290_18
|View full text |Cite
|
Sign up to set email alerts
|

Detection and evaluation of intracranial aneurysms in the posterior fossa by multidetector computed tomography angiography – Comparison with digital subtraction angiography

Abstract: Introduction: Posterior fossa hemorrhages are not so frequent but as posterior cranial fossa space is narrow and has many vital structures, even a small amount of bleed can lead to compression of brain stem and serious consequences. Identification and planning management of cause of bleed requires angiogram. Digital subtraction angiography (DSA) being invasive modality but is gold standard, so noninvasive computed tomography angiography (CTA) is compared to detect cause of bleed in the posterior f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…DSA may lead to ambiguous results due to its inability to project the aneurysm sufficiently. Several factors contribute even technical to this like the location of the aneurysm in vessels bifurcation, regional complex vascular anatomy, vessels arising from the sac and the small size (less than 3 mm) of the aneurysmal sac, rotational limitations of the C-arm fluoroscopy, inadequate projections due to patient incorporation or projections out of the standard protocol [10][11][12] . In addition, mural calcifications, luminal thrombi, proximity to bony structures of the skull base and to the brain parenchyma, may constitute useful information for the treatment planning of some patients and cannot be obtained by DSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSA may lead to ambiguous results due to its inability to project the aneurysm sufficiently. Several factors contribute even technical to this like the location of the aneurysm in vessels bifurcation, regional complex vascular anatomy, vessels arising from the sac and the small size (less than 3 mm) of the aneurysmal sac, rotational limitations of the C-arm fluoroscopy, inadequate projections due to patient incorporation or projections out of the standard protocol [10][11][12] . In addition, mural calcifications, luminal thrombi, proximity to bony structures of the skull base and to the brain parenchyma, may constitute useful information for the treatment planning of some patients and cannot be obtained by DSA.…”
Section: Discussionmentioning
confidence: 99%
“…3D-RA serves as an add-on technique to DSA providing precise measurements necessary for endovascular coiling 14 . CTA based on the three-dimensional algorithms for image post-processing, provides satisfactory sensitivity and additionally possesses the advantage of delineating more accurately the morphological features of the aneurysm than conventional DSA 11 . It is an easy to perform method, timesaving, tolerated well by patients with no contraindications to contrast material and provides an early diagnosis which assists in the decision making process.…”
Section: Discussionmentioning
confidence: 99%
“… 6 CT angiography (CTA) is the primary diagnostic tool to provide anatomic and morphological features of intracranial aneurysms. 7 Zhang et al 8 revealed DD presence, AR, and larger flow angle to be associated with BA tip aneurysm rupture. Most recently, a suggested simple machine-based nomogram based on machine learning constructed to predict aneurysmal rupture risk at different locations achieved accurate results.…”
Section: Introductionmentioning
confidence: 99%